2021
DOI: 10.1016/j.heliyon.2021.e06151
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of primary waste heat boiler tube in ammonia plant

Abstract: The primary Waste Heat Boiler (WHB) in an ammonia plant experienced cap leaking and the outer tube rupture after ten months since the last repair and replacement (total retubing). The leaking cap and the outer tube materials are low carbon steel SA-204 Gr. B and SA-209 Gr. T1a. The inappropriate vertical part of the leaked cap, which is 2.4 mm shorter than the design, might trigger turbulence flow inside the cap and lead to flow-accelerated corrosion (FAC), as suggested by the appearance of wall thinning and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Majumdar & Mukherjee (1988) wrote on the influence of steam injection in primary reformer to the energy efficiency of the overall plant. Failure analysis of NH3 plant primary waste heat boiler and energy-intensive design of the SMR furnace were previously carried out by Ardy et al (2021) and Zecevic (2021) respectively.…”
Section: Primary Reformingmentioning
confidence: 99%
“…Majumdar & Mukherjee (1988) wrote on the influence of steam injection in primary reformer to the energy efficiency of the overall plant. Failure analysis of NH3 plant primary waste heat boiler and energy-intensive design of the SMR furnace were previously carried out by Ardy et al (2021) and Zecevic (2021) respectively.…”
Section: Primary Reformingmentioning
confidence: 99%
“…Numerous studies have shown that the rapid fluid has an adverse effect on the deposition of products at the interface and the presence of bumps around the weld leads to the formation of local turbulence when the liquid flows through [ 14 , 15 , 16 ]. It not only enhances the erosion and corrosion of the pipeline [ 17 , 18 ], but also further alters the microscopic morphology of the interface owing to the change of the corrosion scale. In addition, under the influence of varying flow forms and flow-induced wall shear stress, the deposition rate and dissolution mechanism of the product film on the substrate surface also become more complex [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the design aspects of a shallow-bed reactor involving a swift, diffusion-controlled reaction. Methods for estimating the catalyst bed's mesh count, diameter, height, and volume are discussed [5]. Bartosz et al described the effect of various design changes of the ammonia oxidation reactor in the nitric acid plant on the flow distribution of the air-ammonia mixture.…”
Section: Introductionmentioning
confidence: 99%